Transformational Leadership, Work Environment, Job Satisfaction, And Employee Loyalty: Evidence From PMKS PT Pinago Utama TBK - Mursalinah; Cahyadi, Afriyadi; Margareth, Yomeini (Universitas Muhammadiyah Pontianak, 2026)
Employee loyalty is essential for sustaining organizational performance in the palm oil processing industry. This study examines the effects of transformational leadership, work environment, and job satisfaction on employee loyalty at PMKS PT Pinago Utama Tbk. A quantitative cross-sectional survey was conducted among 172 permanent employees selected through simple random sampling, and the data were analyzed using multiple linear regression. The results show that work environment and job satisfaction positively affect employee loyalty, whereas transformational leadership has no significant effect. Organizations should prioritize supportive working conditions and employee satisfaction to strengthen long-term employee loyalty.